Integrated biomaterials in tissue engineering - Ramalingam, Murugan (Biomaterials science, engineering, and technology., 2012)
"Integrated Biomaterials in Tissue Engineering" features all aspects from fundamental principles to current technological advances in biomaterials at the macro/micro/nano/molecular scales suitable for tissue engineering and regenerative medicine. The book is unique as it provides all important aspects dealing with the basic science involved in structure and properties, techniques and technological innovations in material processing and characterizations, and applications of biomaterials in tissue engineering and regenerative medicine.